Minecraft the manga. 2 - Seto, Kazuyoshi (Viz Media LLC, 2025)
Nico has set off on an adventure to the end of the world! He now has what every great adventurer needs--an adventuring party. Turns out it's good he has friends with him, because he's about to face a spider larger than his whole party combined!